Ekstraksi dan Pemisahan Penisilin G dari Fenilasetat dengan Teknik Membran Cair Emulsi - Imam Santoso; Buchari Buchari; Muhammad Bachri Amran; Aminudin Sulaeman (Jurnal Matematika & Sains, 2007)
The separation and purification of penicillin G from phenyl acetic acid (PAA) is very difficult to be carried out becausethe two compounds are weak acids and the two compounds can change from one to another by influence of pH. The aimof this research is to establish the optimal conditions for the extraction and separation of penicillin G from phenylaceticacid using the emulsion liquid membrane technique. The optimal conditions were ratio of internal phase volume tomembrane phase volume of 1:1; time of stiring for emulsion preparation of 1 minute; emulsion contact rate of 300 rpm;emulsion contact time of 15 minutes; rate of stirring of emulsion of 2000 rpm; rest time of emulsion of 13 minutes;concentration of penicillin G as external phase 375 ppm; and concentration of surfactant 5% (v/v). At these conditionspenicillin G can be extracted and separated from phenylacetic acid with a separation factor of 19.3 and a contact timeof 15 minutes. Thus the technique of emulsion liquid membrane may be used as a reasonably effective method toseparate penicillin G from phenylacetic acid.